Community HIV testing for men who have sex with men: results of a pilot project and comparison of service users with those testing in genitourinary medicine clinics. Issue 2 (5th December 2008) - Bailey, A C; Roberts, J; Weatherburn, P; Hickson, F C I; Reid, D S; Fisher, M; Dean, G
Abstract : Results of a community HIV testing pilot (fasTest) targeting men who have sex with men (MSM) in Brighton are reported and service users are compared with those testing in genitourinary medicine (GUM) clinics. FasTest offers rapid HIV testing in a weekly evening drop-in session staffed by GUM professionals in a community organisation. It was prospectively evaluated from November 2004 to March 2006 using a self-completed paper questionnaire assessing demographics, previous use of GUM, HIV testing history and sexual behaviour. Follow-up through GUM/HIV services was monitored. A simplified questionnaire was completed by MSM accessing the GUM clinic over the same time period. Men were included in the analysis if they identified as gay or bisexual or had recent sex with a man, tested for HIV and received a result. In both the fastest and GUM groups, men reported high rates of unprotected anal sex in the last 3 months. fasTest clients were significantly younger and less likely to test positive for HIV. This difference was independent of age and HIV testing history. There was no difference in rates of recent infection between the two. We conclude that community HIV testing is feasible and reaches the target group of high risk MSM.